Managing Pesticide Risks for Non-Target Ecosystems with Pesticide Risk Indicators: a Multicriteria Approach - Chiara Maria Travisi; Peter Nijkamp; Marco Vighi; Paolo Giacomelli (Tinbergen Institute, 2004)
In the search for effective pesticide risk management tools, the design of pesticide risk indicators is nowadays receiving increasing attention as a complement to more established regulatory strategies. In the present paper, we apply some recently developed pesticide risk indices and test their potential for management purposes. A pilot approach is proposed, which explores pesticide worst-case hazard scenarios at different space-time scales by means of a set of 5 ecotoxicological risk indices. The results are then interpreted from the perspective of a decision support method using the so-called Critical Threshold Value approach. Our risk analysis is then enriched within a multicriteria framework which integrates environmental, agronomic and economic objectives.
Keywords: Q16; Q24; Q25; R38; H8; 330; pesticides; hazard and risk assessment; risk indices; decision support tools; multicriteria analysis; Pestizid; Risikomanagement